Studying the effect of spiritual leadership on organizational performance: an empirical study in hotel industry. Issue 3 (3rd August 2015) - Salehzadeh, Reza; Khazaei Pool, Javad; Kia Lashaki, Jafar; Dolati, Hasan; Balouei Jamkhaneh, Hadi
<x content-type="archive" xml:space="preserve">Abstract</x> Purpose – The purpose of this paper is to investigate the effect of spiritual leadership on organizational performance based on the balanced scorecard (BSC). Design/methodology/approach – Statistical population includes the middle managers of 60 hotels across eight provinces in Iran. For data analysis, 207 accurate completed questionnaires have been used. Structural equation modeling has been used to explore the relationships between the research variables. Findings – The findings showed that spiritual leadership has a significant positive effect on calling and membership. Also, spiritual leadership, calling and membership have a significant positive effect on organizational performance. Originality/value – This paper by presenting a comprehensive model provides a framework and approach for studying the performance consequences of spiritual leadership in the hotel industry using the BSC.